Partially reduced graphene oxide produced by glucose in alkaline conditions using probe sonication: the role of the base in reduction - Uchôa Teixeira, Jean Valdir [UNESP]; Cavalcante Pimentel, Gabriel Junior [UNESP]; Santos, Adriana Alencar [UNESP]; Gonçalves Dias, Leonardo Francisco [UNESP]; Mastelaro, Valmor Roberto; Lisboa-Filho, Paulo Noronha [UNESP] (Elsevier, 2023)
The use of mild reagents in the synthesis of reduced graphene oxide (RGO) is an advantageous method to produce materials partially reduced without the use of hazardous chemicals, such as the hydrazine route, which is a standard method to promote the chemical reduction of graphene oxide. This paper presents the sono-assisted route to produce partially RGO particles using glucose as a mild reducing agent in alkali media, mediated by sodium and potassium hydroxide. The results demonstrated the direct influence of base on the final properties of RGO, with differences in the thermal stability, bandgap, impedance, and C/O rate. With a possible anchoring of glucose-derivated molecules on sheet surface, this study indicates a way to control the particle surface properties according to the base chosen during the sono-assisted reduction method.
Keywords: Chemical reduction; Glucose; Reduced graphene oxide; Sono-assisted reduction